2012
DOI: 10.1371/journal.pone.0044226
|View full text |Cite
|
Sign up to set email alerts
|

Cyclohexyl Ketone Inhibitors of Pin1 Dock in a Trans-Diaxial Cyclohexane Conformation

Abstract: Cyclohexyl ketone substrate analogue inhibitors (Ac–pSer-Ψ[C = OCH]-Pip–tryptamine) of Pin1, the cell cycle regulatory peptidyl-prolyl isomerase (PPIase), were designed and synthesized as potential electrophilic acceptors for the Pin1 active site Cys113 nucleophile to test a proposed nucleophilic addition-isomerization mechanism. Because they were weak inhibitors, models of all three stereoisomers were docked into the active site of Pin1. Each isomer consistently minimized to a trans-diaxial cyclohexane confor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…(22) Similarly, poor inhibition of Pin1 by cyclohexyl ketone inhibitors suggested that the nucleophilic addition mechanism with the Pin1 Cys113 thiol is unlikely. (23)…”
mentioning
confidence: 99%
“…(22) Similarly, poor inhibition of Pin1 by cyclohexyl ketone inhibitors suggested that the nucleophilic addition mechanism with the Pin1 Cys113 thiol is unlikely. (23)…”
mentioning
confidence: 99%
“…By variation of these ground state analogs, the same lab developed phosphorylated transition state inhibitors for Pin1 . Moreover, the Etzkorn group described cyclohexyl ketone Inhibitors of Pin1 that dock in a trans-diaxial conformation to the Pin1 active site in crystal structures (Xu et al, 2012). The information obtained from these inhibitors verified the twisted-amide mechanism for Pin1 catalysis.…”
Section: Peptidic Inhibitors and Substrate Analogsmentioning
confidence: 91%
“…In a series of publications, Felicia Etzkorn and her coworkers finally verified the non-covalent mechanism. They used transition state inhibitors (Xu et al, , 2012 of Pin1 to confirm a twisted amide ω-90°-syn-exo transition state conformation (Mercedes-Camacho et al, 2013). Based on these measurements a transition state was proposed that is stabilized by an intramolecular hydrogen bond from the amide Pro +1 to the prolyl nitrogen ( Figure 6).…”
Section: Catalytic Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…PIN1 is overexpressed in breast cancer and is related to mammary tumor growth, and epithelial-mesenchymal transition, and natural and synthetic inhibitors are being probed to control its activity[ 55 , 57 , 80 - 87 ]. Similarly, LMTK3 overexpression stimulates cellular proliferation and tumor formation, and correlates with shorter survival times in ERα+ breast cancer, and resistance to Tam treatment, but these events are reduced when LMTK3 expression is decreased[ 58 , 88 - 90 ].…”
Section: Erα Polyubiquitination Inhibition In Breast Cancer As a Key mentioning
confidence: 99%